Exploring Economic Growth and Development Strategies in South Korea and Nepal: Evaluating Risk and Opportunities in Investment Narratives - Chaudhary, Newal (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
This article explores the narratives of investment in South Korea and Nepal, examining the risks and opportunities associated with each country. The study is based on a comprehensive review of existing literature, including academic research, government reports, and news articles. The analysis reveals that while South Korea is widely considered a safe and stable investment destination, with a well-developed infrastructure, skilled workforce, and strong regulatory framework, Nepal presents a more complex and challenging investment landscape, characterized by political instability, weak governance, and inadequate infrastructure. However, the study also uncovers a range of unique investment opportunities in Nepal, particularly in the areas of renewable energy, tourism, and agriculture. The article concludes by offering insights and recommendations for investors seeking to navigate these complex and dynamic markets. The findings suggest that while South Korea is widely perceived as a relatively safe and attractive destination for investment, with a highly developed economy and supportive government policies, Nepal faces greater challenges and uncertainties, including political instability, inadequate infrastructure, and limited access to financing. The study also highlights several areas of potential opportunity for investors in both countries, including in emerging industries such as renewable energy and technology, as well as in sectors such as tourism and agriculture. The study concludes with a discussion of the implications of these findings for investors and policymakers, and suggests areas for further research and analysis.